The Social Role of Vocal Complexity in Striped Dolphins - Papale, Elena; Fanizza, Carmelo; Buscaino, Giuseppa; Ceraulo, Maria; Cipriano, Giulia; Crugliano, Roberto; Grammauta, Rosario; Gregorietti, Martina; Renò, Vito; Ricci, Pasquale; Santacesaria, Francesca C.; Maglietta, Rosalia; et al. (Frontiers in Marine Science, 2020)
Many gregarious species require complex patterns of communication for maintaining coordinated behaviors, articulated social structure and group cohesion. In mammal species, social complexity has been considered the driving force for the development of advanced acoustic communication systems. Striped dolphins are highly social, showing large group size with females maintaining strong bonds with kin. Here, we tested the hypothesis that more complex acoustic pattern plays a key role in social activity in the striped dolphins. The production rate of clicks, whistles and burst pulses, and the acoustic features of whistles have been related to the activity context (feeding, travelling, resting and socializing). Furthermore, complex calls, consisting of a combination of frequency-modulated, and/or pulsed components were detected. Higher whistles and burst pulses production rates were recorded during socializing. Also, the social activity can be discriminated basing on the modulation of the whistle contour. Biphonic calls were especially recorded during social interaction events, suggesting that these phenomena can encode information about individual or group identity to conspecifics. Outcomes indicate the pivotal role of vocal complexity during social context and elicit further investigations of the communication system of small odontocetes from local to wider spatial scale.